China's International Competitiveness: Reassessing the Evidence - Ari Van Assche; Chang Hong; Veerle Slootmaekers (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
In this paper we argue that export data are an inadequate tool to measure a country's international competitiveness when external trade is dominated by export-processing trade. Export data do not necessarily reflect the value produced in an exporting country, but rather capture the gross value of the products that leave a country's ports. We demonstrate that, in the case of China, this leads to an upward bias in both the perceived quantitative and qualitative threats to the Western economies.
Keywords: 330; China; export-processing trade; technological intensity; trade balance; Internationaler Wettbewerb; Messung; China